Corporate Social Responsibility in Garment Industry Supply Chain - Hasan, M; Shi, Y (Archives of Business Research, 2017)
There has been a growing concern over the ready-made garment (RMG) industry in their environmental and social performance. Each stakeholder involved in the garment supply chain has embarked on Corporate Social Responsibility (CSR) practices in responding to the criticism of poor working conditions. This thesis reviews the history of the RMG industry and highlights the problems such as environmental issues, workers’ low wages and hazardous work environment raised with the development of the garment industry in developing countries. CSR concept is reviewed from the aspects of its importance, implementation and related challenges. Some of the main apparel exporters (e.g. China, India and Bangladesh) are analyzed in their current situation of the industry and related CSR practices. It is found that CSR is still at an early stage, regulations are generally not comprehensive and workers are in poor working conditions in the RMG industry of developing countries. Based on what are found in the different cases, the collaboration between each stakeholder seems of importance to improve current conditions. Not only garment manufacturers themselves, but also the government, buyers, none-government organizations (NGO) and consumers are responsible for supporting the RMG industry towards a more socially responsible direction. A framework is established to illustrate the relationship and necessary collaboration between the stakeholders.